1972
DOI: 10.1002/bit.260140511
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of C. pyrenoidosa using 94% 13C CO2

Abstract: SummaryThe alga Chlorella pyrenoidosa has been grown in mass quantities on 94 at. yo W02.Neither inhibition nor a requirement for adaptation was encountered; changes in morphology were not evident. A statistically significant increase in mass of cells produced in the presence of W O z was observed.The algal cells have been labeled to the 90 at. % I3C level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…It has also been established that 40% of brain hydrogen but only 10% of fatty acid hydrogen is derived from body water (for most tissues this figure is 20-30%). (51) In some reactions where radical or ion-radical intermediate state is involved, nuclear spin-selective processes (the magnetic IE (19) ) can play an important role; for example, phosphorylation reactions (52) can have 2.6-fold higher yields when nuclear spin-possessing 25 Mg 2þ ions are used instead of the spinless 24 Mg isotope. (53) Regrettably there are currently no data on isotope discrimination by living organisms based on this intriguing variety of the IE.…”
Section: Seamentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been established that 40% of brain hydrogen but only 10% of fatty acid hydrogen is derived from body water (for most tissues this figure is 20-30%). (51) In some reactions where radical or ion-radical intermediate state is involved, nuclear spin-selective processes (the magnetic IE (19) ) can play an important role; for example, phosphorylation reactions (52) can have 2.6-fold higher yields when nuclear spin-possessing 25 Mg 2þ ions are used instead of the spinless 24 Mg isotope. (53) Regrettably there are currently no data on isotope discrimination by living organisms based on this intriguing variety of the IE.…”
Section: Seamentioning
confidence: 99%
“…Neither inhibition nor a requirement for adaptation is encountered when alga is grown on 13 CO 2 , with no observable morphological changes. (24) High concentrations of D 2 O are known to cause some abnormalities, but the simultaneous presence of 13 C can diminish this, at least in alga. (21,25) The toxicity of 13 C-labeled markers, as potential replacements for radioactive labeling, was tested on mice.…”
mentioning
confidence: 98%
“…In biological systems, each of the four most abundant elements (C, H, O and N) has more than one stable isotope, the lighter one being the most abundant (e.g., the share of 12 C is 98.9%). Microbes, plants and animals, including mammals, can grow in an environment with signi cantly altered ratios of stable isotopes compared to natural, but the phenotype of the organisms can be signi cantly affected [7][8][9][10][11][12][13][14] . The researchers concluded that the "organisms of different isotopic compositions are actually different organisms, to the degree that their isotopic compositions are removed from naturally occurring compositions" 10 .…”
Section: Introductionmentioning
confidence: 99%
“…After a period of adaptation (“lag phase”), growth resumes, but the rate is usually slower than in normal isotopic environment [8] . The changes in the growth rate can be explained by the impact of isotopic substitutions on the kinetics of enzymes [9] , pattern of hydrogen bonds and similar relatively subtle but cumulatively potentially important effects.…”
Section: Introductionmentioning
confidence: 99%